Innovation As a Factor of Economic Development: A Comparative Analysis of Economic Theories of Joseph Schumpeter and Mariana Mazzucato - Sylwia STEFANIAK (Communications of International Proceedings, 2022)
The purpose of this paper is to describe the foundations of economic theory on innovation using the works of Joseph A. Schumpeter and Mariana Mazzucato as examples. This characterization will support my subsequent activities related to the realization of my doctoral dissertation, the main objective of which is the implementation of the "Policy for the development of artificial intelligence in Poland from 2020" through the modeling and implementation of program activities supporting the implementation of new technologies in the sector of small and medium-sized enterprises (hereinafter: SMEs), including the involvement of key market players involved in such initiatives. The juxtaposition of the theories of these two economists is important in my research work insofar as they justify the research gap indicating the legitimacy of active participation in the development and implementation of innovative solutions, as well as cooperation between the private and public sector in particular in the field of artificial intelligence. In this paper, I have used the comparative methodology of both economists, which ultimately allows me to preliminarily orient my further research towards specific solutions in the SME sector.
Keywords: innovation; artificial intelligence; public policy